2021
DOI: 10.1111/nicc.12649
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses' experiences of working in the intensive care unit during the COVID‐19 pandemic

Abstract: Background During the pandemic, increased numbers of patients requiring intensive care unit (ICU) admission required an increase in ICU capacity, including ICU staffing with competence to care for critically ill patients. Consequently, nurses from acute care areas were called in to staff the ICU along with experienced intensive care nurses. Aims and objectives To describe Swedish registered nurses' experiences of caring for patients with COVID‐19 in ICUs during the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
236
0
26

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(269 citation statements)
references
References 20 publications
7
236
0
26
Order By: Relevance
“…This balancing act between work and personal life can threaten nurses’ health, leading to emotional exhaustion [ 22 ]. That this aspect of conscience was experienced as most stressful is not surprising, and can be an explanation to earlier studies reporting that working in a COVID-ICU has a high impact on the mental well-being of nurses [ 13 19 ]. Another aspect of sense of conscience “forced to provide care that felt wrong in the Covid-ICU” was highly rated and aligns with other research such as the Sugg et al [ 4 ] study about missed care among “COVID-nurses.” They found that the “COVID-nurses” struggled to support patients’ emotional wellbeing and mental health, and felt that they were unable to provide usual levels of support, reassurance, and interaction with patients.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…This balancing act between work and personal life can threaten nurses’ health, leading to emotional exhaustion [ 22 ]. That this aspect of conscience was experienced as most stressful is not surprising, and can be an explanation to earlier studies reporting that working in a COVID-ICU has a high impact on the mental well-being of nurses [ 13 19 ]. Another aspect of sense of conscience “forced to provide care that felt wrong in the Covid-ICU” was highly rated and aligns with other research such as the Sugg et al [ 4 ] study about missed care among “COVID-nurses.” They found that the “COVID-nurses” struggled to support patients’ emotional wellbeing and mental health, and felt that they were unable to provide usual levels of support, reassurance, and interaction with patients.…”
Section: Discussionmentioning
confidence: 68%
“…It is important to analyze if there are any differences in how the nurses experienced their care encounters and stress of conscience when working in a COVID-ICU compared to their usual workplace. Colleagues working in a COVID-ICU have reported that they could not provide all of the care that they should have, i.e., missed care, and expressed alarm over the frequency of occurrence [ 13 ]. Therefore, due to the higher acuity of care, we included the item “Every hour”.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is to the best of our knowledge among the rst to evaluate the impact of critical care sta ng on the outcomes of critically ill patients during a pandemic. There have been reports highlighting the importance of the nurse-to-patient ratio on the quality of critical care [37][38][39], but most, if not all of them, had been performed outside pandemic conditions [6,27,40]. Usually, studies compared patient outcomes across ICU centres that are run with different sta ng ratio [41,42].…”
Section: Discussionmentioning
confidence: 99%